International Law And The Responsibility To Protect: Legal And Theoretical Basis For International Intervention In Nigeria - Ajigboye, Oyeniyi (Journal of Sustainable Development Law and Policy, 2025)
One of the primordial aims of international law is to foster international co-operation, peace, security and amicable relations among nations of the world. Internal conflicts, however, continue to pose threat to the international order and development globally. Consequently, the Responsibility to Protect (R2P) principle has recently gained recognition as an emerging norm of international law that enjoins the international community to intervene when countries fail to protect their populations from mass atrocity crimes namely: genocide, crimes against humanity, war crimes and ethnic cleansing. One of the key foundations of the emerging R2P norm is the principle of intervention which allows international action whenever it is necessary and justifiable to reduce or resolve internal conflict among the constituent States of the world. Despite the growing application of the norms of intervention in international law, its practical implementation and effects have been received with mixed feelings. There are especially, questions whether interventions really aid or hinder international peace and security, although it may be functional to avert apparent helpless situations. This paper examines the imperatives of intervention in internal conflicts and its continued relevance in international law. It also comments on the applicability and desirability of international intervention in Nigeria in response to the Boko Haram conundrum. It argues that although intervention is appropriate as it were to protect Nigerian citizens from Boko Haram in the apparent failure of the Nigerian government so to do, international intervention should be properly regulated to ensure that it is not used as a tool to jeopardize sustainable development in Nigeria as well as in other developing countries.